2020
DOI: 10.1055/a-1207-1006
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions in Adults – a Differential Diagnostic Approach

Abstract: Objective Cerebral white matter lesions on MRI in adults are a common finding. On the one hand, they may correspond to a clinically incidental feature, be physiologically or age-associated, or on the other hand they may be the overture to a severe neurological disease. With regard to pathophysiological aspects, practical hints for the differential diagnostic interpretation of lesions in daily clinical practice are presented. Material and Methods With special regard to the vascular architecture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 81 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…Cerebral amyloid plaques are rarely found in white matter (118), but our finding suggests that the Aβ deposits may pertain to vascular Aβ localized in capillaries and blood vessels (119)(120)(121)(122). It would be interesting to investigate these subcortical Aβ-associated vascular microenvironments, given their putative contribution in white matter hyperintensity and cerebrovascular dysfunction in AD (123)(124)(125)(126)(127)(128). Second, while our categorical pathology classification approach allowed us to identify DEGs associated with different pathological microenvironments, we acknowledge it may not address the full spatial heterogeneity of AD pathology, and in the future, more complex modeling approaches could be implemented.…”
Section: Discussionmentioning
confidence: 85%
“…Cerebral amyloid plaques are rarely found in white matter (118), but our finding suggests that the Aβ deposits may pertain to vascular Aβ localized in capillaries and blood vessels (119)(120)(121)(122). It would be interesting to investigate these subcortical Aβ-associated vascular microenvironments, given their putative contribution in white matter hyperintensity and cerebrovascular dysfunction in AD (123)(124)(125)(126)(127)(128). Second, while our categorical pathology classification approach allowed us to identify DEGs associated with different pathological microenvironments, we acknowledge it may not address the full spatial heterogeneity of AD pathology, and in the future, more complex modeling approaches could be implemented.…”
Section: Discussionmentioning
confidence: 85%
“…One important take-away that they discuss for all incidental findings holds true for non-specific WMSAs as well: image resolution (signal to noise ratio, spatial resolution) seems to play an important role with regard to reported rates. In addition, layer gaps in 2D as opposed to 3D images can result in smaller lesions being missed [5]. Whether or not these supposably "non-specific" findings could still be related to certain pathologies remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is widely used for the identification of white matter pathologies with the presence of visible white matter signal abnormalities (WMSAs). Signals from standard imaging sequences, such as T2-weighted (T2W), T1-weighted (T1W), and fluid-attenuated inversion recovery (FLAIR) can be used to evaluate their patterns [1][2][3][4][5][6]. The spectrum of underlying pathologies itself is broad [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that lesions of U-fibers can help to distinguish between WM disease of presumed vascular origin and demyelinating WM disease ( 12 , 28 ). In T2-weighted fluid-attenuated inversion recovery (T2 FLAIR) images of patients with demyelinating WM disease, WM hyperintensities (WMHs) are commonly observed involving U-fibers and may cause changes in the dMRI properties of U-fibers ( 11 , 29 , 30 ). However, in those WM diseases of presumed vascular origin, WMHs generally do not involve U-fibers due to the presence of blood supply compensation and the relative absence of damage to U-fibers ( 8 , 12 , 31 ).…”
Section: Introductionmentioning
confidence: 99%